Flattening and Unpacking Human Genetic Variation in Mexico, Postwar to Present. Issue 1 (11th April 2017) - Anaya-Muñoz, Víctor Hugo; García-Deister, Vivette; Suárez-Díaz, Edna
Argument: This paper analyzes the research strategies of three different cases in the study of human genetics in Mexico – the work of Rubén Lisker in the 1960s, INMEGEN's mapping of Mexican genomic diversity between 2004 and 2009, and the analysis of Native American variation by Andrés Moreno and his colleagues in contemporary research. We make a distinction between an approach that incorporates multiple disciplinary resources into sampling design and interpretation ( unpacking ), from one that privileges pragmatic considerations over more robust multidisciplinary analysis ( flattening ). These choices have consequences for social, demographic, and biomedical practices, and also for accounts of genetic variation in human populations. While the former strategy unpacks fine-grained genetic variation – favoring precision and realism, the latter tends to flatten individual differences and historical depth in lieu of generalization.